Breeding System, Flower Visitors and Seedling Survival of Two Endangered Species of Helianthemum (Cistaceae) - RODRÍGUEZ-PÉREZ, JAVIER (Ann Bot, 2005)
• Background and Aims Helianthemum marifolium and H. caput-felis are two endangered plant species of the western Mediterranean. Several aspects of the reproduction of both species were examined to determine whether their rarity could be related to factors causing reproductive limitation. • Methods The flowering and fruiting phenology of both species in two non-sympatric island populations (Mallorca, Balearic Islands, western Mediterranean) were compared. Hand-pollination experiments were conducted to determine their fruit and seed production under different pollen sources. The composition of the pollinator assemblage and the effect of temporal variation and sun exposure on reproductive output and seedling survival were also investigated. • Key Results Flowering periods were longer for H. marifolium than for H. caput-felis in the populations studied. Helianthemum marifolium is mostly an outbreeder, i.e. fruit and seed set was three-fold higher when pollen came from other plants. In H. caput-felis, neither fruit nor seed set was affected by pollination treatments. Flower visitors were more diverse for H. caput-felis than for H. marifolium. In both species, most floral visits were made by hymenopterans. The total number of pollinator visits varied significantly between years, decreasing more than two-fold from 2001 to 2002, in both species. In agreement with its outbreeder character, variation in reproductive output between years was also observed in H. marifolium. It showed a 50 % decrease in fruit set in 2002, a pollinator-poor year. Finally, seedling survival increased three- to six-fold from 2001 to 2002. A correlation between seedling size and survival had also been detected. • Conclusions Reproductive limitations were detected for neither species (i.e. fruit and seed set, pollination service and seedling survival on natural populations). Hence, the increasing rarity of these two species is probably a direct result of the destruction of their habitat.